Chitosan 3D cell culture system promotes naïve-like features of human induced pluripotent stem cells: A novel tool to sustain pluripotency and facilitate differentiation. (January 2021) - Chang, Po-Hsiang; Chao, Hsiao-Mei; Chern, Edward; Hsu, Shan-hui
Abstract: A simplified and cost-effective culture system for maintaining the pluripotency of human induced pluripotent stem cells (hiPSCs) is crucial for stem cell applications. Although recombinant protein-based feeder-free hiPSC culture systems have been developed, their manufacturing processes are expensive and complicated, which hinders hiPSC technology progress. Chitosan, a versatile biocompatible polysaccharide, has been reported as a biomaterial for three-dimensional (3D) cell culture system that promotes the physiological activities of mesenchymal stem cells and cancer cells. In the current study, we demonstrated that chitosan membranes sustained proliferation and pluripotency of hiPSCs in long-term culture (up to 365 days). Moreover, using vitronectin as the comparison group, the pluripotency of hiPSCs grown on the membranes was altered into a naïve-like state, which, for pluripotent stem cells, is an earlier developmental stage with higher stemness. On the chitosan membranes, hiPSCs self-assembled into 3D spheroids with an average diameter of ~100 μm. These hiPSC spheroids could be directly differentiated into lineage-specific cells from the three germ layers with 3D structures. Collectively, chitosan membranes not only promoted the naïve pluripotent features of hiPSCs but also provided a novel 3D differentiation platform. This convenient biomaterial-based culture system may enable the effective expansion and accessibility of hiPSCs for regenerative medicine, disease modeling, and drug screening.